Digestibilidade e tempo de trânsito gastrintestinal de dietas contendo níveis crescentes de fibra bruta para pacu - Rodrigues, Laurindo André; El Hadi Perez Fabregat, Thiago [UNESP]; Fernandes, João Batista Kochenborger [UNESP]; Nascimento, Thiago Matias Torres [UNESP]; Sakomura, Nilva Kasue [UNESP] (Universidade Estadual de Maringa, 2010)
This work aimed to evaluate the effect of increasing dietary fiber levels on the digestibility and gastrointestinal transit time (GTT) for pacu. The digestibility trial used 288 pacu in a completely randomized design, fed in aquaria and transferred to a modified Guelf-type feces collector, using the partial sampling method. The inert marker on the diets was chromic oxide (1%) to establish the diet digestibility. In the GTT assay, 288 pacu were distributed in 24 aquaria in a completely randomized design. Fish were fed with two colored diets - green and white - and feces color was determined after abdominal pressure. The white and green diets used 1% of titanium and chromic oxides, respectively. Total GTT was determined when all fish showed green feces. The apparent digestibility coefficients and GTT of diets decreased as dietary fiber levels increased. These results indicated that 9% dietary fiber can be used in pacu diets without negative effects on energy, protein, crude fiber and ether extract digestibility and GTT.
Digestibility and gastrointestinal transit time of diets with increasing dietary fiber levels to pacu
Keywords: Native fish; Nutrition; Piaractus mesopotamicus